2019
DOI: 10.1111/desc.12811
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of orienting to walking direction in 6‐month‐old infants: An ERP study

Abstract: The ability to detect social signals represents a first step to enter our social world. Behavioral evidence has demonstrated that 6‐month‐old infants are able to orient their attention toward the position indicated by walking direction, showing faster orienting responses toward stimuli cued by the direction of motion than toward uncued stimuli. The present study investigated the neural mechanisms underpinning this attentional priming effect by using a spatial cueing paradigm and recording EEG (Geodesic System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…This finding replicates and extends earlier demonstrations of a validity effect at the level of the occipital P1 in response to peripheral targets appearing soon after a peripheral cue (Richards, 2005), or a dynamic central cue whose movement is spatially informative with respect to the target position (Lunghi et al, 2019(Lunghi et al, , 2020Natale et al, 2017). Critically, the current results extend these earlier demonstrations by showing that even spatially noninformative central cues are capable of orient infants' visual attention toward the left or right side of space.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding replicates and extends earlier demonstrations of a validity effect at the level of the occipital P1 in response to peripheral targets appearing soon after a peripheral cue (Richards, 2005), or a dynamic central cue whose movement is spatially informative with respect to the target position (Lunghi et al, 2019(Lunghi et al, , 2020Natale et al, 2017). Critically, the current results extend these earlier demonstrations by showing that even spatially noninformative central cues are capable of orient infants' visual attention toward the left or right side of space.…”
Section: Discussionsupporting
confidence: 91%
“…In these studies, ERP responses to peripheral target objects were modulated by the congruent versus incongruent relation between the directionality (leftward or rightward) of the dynamic social cue and the position of the target object. In particular, Lunghi et al (2019) reported a larger P1 amplitude over occipital-parietal sites in response to peripheral targets appearing at locations congruent with the walking direction of the point-light displays, indicating the enhancement of information processing at the attended location induced by the central cue.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Source estimation has not been frequently reported in the infant EEG literature, with the notable exception of a few research groups that used volumetric approaches such as CDR with realistic head models built from MRIs of head-size-matched individuals ( Xie and Richards, 2017 ) or from age-matched MRI averages ( Lunghi et al, 2019 ), or using ECD with a four-shell ellipsoidal head model ( Ortiz-Mantilla et al, 2019 ). Source imaging is more frequently used in magnetoencephalography (MEG) ( Kao and Zhang, 2019 ), but it generally relies on over simplistic spherical models to overcome the absence of realistic head models ( Imada et al, 2006 ; Kuhl et al, 2014 ) or it uses custom-built subject-specific head models that are not reusable by the research community ( Ramírez et al, 2017 ; Travis et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%